2018
DOI: 10.1038/s41598-018-22103-4
|View full text |Cite
|
Sign up to set email alerts
|

Fat accretion measurements strengthen the relationship between feed conversion efficiency and Nitrogen isotopic discrimination while rumen microbial genes contribute little

Abstract: The use of biomarkers for feed conversion efficiency (FCE), such as Nitrogen isotopic discrimination (Δ15N), facilitates easier measurement and may be useful in breeding strategies. However, we need to better understand the relationship between FCE and Δ15N, particularly the effects of differences in the composition of liveweight gain and rumen N metabolism. Alongside measurements of FCE and Δ15N, we estimated changes in body composition and used dietary treatments with and without nitrates, and rumen metageno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(36 reference statements)
3
4
0
Order By: Relevance
“…Interestingly the response of FCE to Δ 15 Nanimal-diet variation at the individual level was almost identical with both statistical approaches used here (slope of -0.033 kg/kg [eq. 4; Table 2] and -0.034 kg/kg [Figure 4A]) and very close to the response of NUE to Δ 15 Nanimal-diet variations previously found by meta-analysis (-0.035 kg/kg; Cantalapiedra-Hijar et al, 2018).…”
Section: The Ability Of N Isotopic Fractionation Vs Plasma Urea To Reflect Dietary and Between-animal Variation In Feed Efficiencysupporting
confidence: 84%
“…Interestingly the response of FCE to Δ 15 Nanimal-diet variation at the individual level was almost identical with both statistical approaches used here (slope of -0.033 kg/kg [eq. 4; Table 2] and -0.034 kg/kg [Figure 4A]) and very close to the response of NUE to Δ 15 Nanimal-diet variations previously found by meta-analysis (-0.035 kg/kg; Cantalapiedra-Hijar et al, 2018).…”
Section: The Ability Of N Isotopic Fractionation Vs Plasma Urea To Reflect Dietary and Between-animal Variation In Feed Efficiencysupporting
confidence: 84%
“…Ruminants live in a symbiotic relationship with their rumen microbiota (comprising bacteria, protozoa, fungi, and archaea), which produce enzymes able to digest their food by breaking down complex polysaccharides of the plant biomass into volatile fatty acids (VFA), microbial proteins, and vitamins (Russell and Hespell, 1981; Bergman, 1990; Van Soest, 1994). Thus, the rumen microbiota fermentation profile has a significant influence on the feed conversion efficiency of the host (Russell, 2001; Li et al, 2009; Hernandez-Sanabria et al, 2011; Jami et al, 2014; Sasson et al, 2017; Meale et al, 2018) and is accountable for up to 70% of the host’s daily energy requirements (Bergman, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…live weight gain/dry matter intake) in cattle and sheep (Wheadon et al 2014;Cheng et al 2015). Recent work indicated that fat measurements strengthen the relationship between cattle FCE and plasma Δ15N (Meale et al 2018). This study aimed to determine whether sheep body composition measurements can strengthen the relationship between FCE and plasma Δ15N.…”
Section: In Vitro Gas Production Of Hydroponic Green Forage From Corn Oat and Barley Seedmentioning
confidence: 97%
“…Individually housed lambs were adapted to the trial diets for 14days. Wool growth was measured using the dye-band technique (Meale et al 2014), whereby a band of black commercial hair dye was applied to the mid-side of each lamb on Day 0. After an experimental period of 11weeks, wool was clipped from the dye-band site and analysed for wool yield and quality parameters.…”
Section: Sensing the Temperature And Humidity Inside Wool Balesmentioning
confidence: 99%
See 1 more Smart Citation